2021
DOI: 10.3390/ijms22095004
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod Following Inoculation of Arabidopsis with Pyricularia oryzae (syn. Magnaporthe oryzae) Influences on the Plant–Pathogen Interaction

Abstract: In plant–pathogen interactions, a proper light environment affects the establishment of defense responses in plants. In our previous experiments, we found that nonhost resistance (NHR) to Pyricularia oryzae Cav. in Arabidopsis thaliana (L.) Heynh. (Arabidopsis), in diurnal conditions, varies with the inoculation time. Moreover, we indicated that the circadian clock plays an important role in regulating time-of-day differences in NHR to P. oryzae in Arabidopsis. However, the involvement of photoperiod in regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…An increase of pathogen resistance after photoperiod stress in Arabidopsis was not only observed after Pseudomonas infection (this study) but also after infection with the hemi-biotrophic fungus P. oryzae (syn. M. oryzae ) ( Shimizu et al, 2021 ) and after infection by the necrotrophic fungus B. cinerea ( Cagnola et al, 2018 ). In these studies short day-grown plants were transferred to long day conditions just before infection, which corresponds to a photoperiod stress treatment and resulted in an increased resistance against P. oryzae and B. cinerea .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase of pathogen resistance after photoperiod stress in Arabidopsis was not only observed after Pseudomonas infection (this study) but also after infection with the hemi-biotrophic fungus P. oryzae (syn. M. oryzae ) ( Shimizu et al, 2021 ) and after infection by the necrotrophic fungus B. cinerea ( Cagnola et al, 2018 ). In these studies short day-grown plants were transferred to long day conditions just before infection, which corresponds to a photoperiod stress treatment and resulted in an increased resistance against P. oryzae and B. cinerea .…”
Section: Discussionmentioning
confidence: 99%
“… Cagnola et al (2018) showed that transferring short day-grown Arabidopsis to long day photoperiod enhanced the resistance to the necrotrophic fungus Botrytis cinerea due to an improvement of the JA-related plant defense. Similarly, Shimizu et al (2021) showed that plant resistance to the hemibiotrophic fungus Pyricularia oryzae (syn. Magnaporthe oryzae ) was enhanced when a light period followed evening inoculations instead of the normal dark period.…”
Section: Introductionmentioning
confidence: 99%
“…Transferring Arabidopsis from a short to a long photoperiod enhanced the resistance to the necrotrophic fungus Botrytis cinerea ( Cagnola et al, 2018 ) and the hemibiotrophic fungus Pyricularia oryzae (syn. Magnaporthe oryzae ) ( Shimizu et al, 2021 ). In the latter case, the outcome of early plant–pathogen interactions was influenced by the length of the photoperiod following inoculation.…”
Section: The Photoperiod Influences Responses To Abiotic and Biotic Stressesmentioning
confidence: 99%
“…In the latter case, the outcome of early plant–pathogen interactions was influenced by the length of the photoperiod following inoculation. The plant resistance to fungus penetration was enhanced, if a light period followed evening inoculations instead of the normal dark period ( Shimizu et al, 2021 ).…”
Section: The Photoperiod Influences Responses To Abiotic and Biotic Stressesmentioning
confidence: 99%
“…That ROS have a role in seasonal switching is hardly novel. Indeed NOX enzymes, which have a long evolutionary history ( 141 ), participate in seasonal modulation of life forms including many plants ( 142 ) and invertebrates ( 143 ) that evolved well before mammals. And in amphibians NOX-derived ROS contribute to different kinds of phenotypic switching at large (i.e., not specific to photoperiod) such as that involving Xenopus tadpole tail regeneration ( 144 ) and amphibian metamorphosis ( 145 ).…”
Section: The Anterior Bed Nucleus Of the Stria Terminalis (Abnst) As ...mentioning
confidence: 99%